A snapshot of nitrogen balance in endurance-trained women - Houltham, S. D.; Rowlands, D. S. (Applied Physiology, Nutrition, and Metabolism, 2014)
Indirect estimates of the mean daily protein requirement for female endurance athletes are 1.2-1.4 g/kg/day; however, an empirical estimate using nitrogen balance is absent. A 72-h nitrogen balance was determined during the mid-follicular phase of 10 female cyclists and triathletes training for 10.8 h/week (SD 2.8) following 2 habituated protein intakes: (i) normal habitual (NH) (protein 85 g/day), and (ii) isocaloric high-protein (HP) (2-fold increase in protein). Total 72-h nitrogen intake was determined from Leco total combustion of ingested food samples. Nitrogen loss was determined from micro-Kjeldahl analysis of 72-h total urinary nitrogen and representative resting and exercise sweat output, plus estimates for fecal and miscellaneous losses. Habituated (steady state) protein requirement was estimated from the mean regression of adapted nitrogen balance vs nitrogen intake. Mean (SD) 24-h dietary protein and energy intake was NH: 1.4 g/kg/day (0.2), energy: 9078 kJ/day (1492), HP: 2.7 g/kg/day (0.3) 8909 kJ/day (1411). Average 24-h urinary nitrogen and sweat urea nitrogen outputs were 13.2 g/day (2.4) and 0.33 g/day (0.08) in NH; 21.5 g/day (3.9) and 0.54 g/day (0.12) in HP, respectively. Nitrogen balance was negative in NH (-0.59 gN/day SD 1.64) but positive in HP (2.69 gN/day SD 3.09). Estimated mean protein requirement was 1.63 g/kg/day (95% confidence interval: 1.1-3.8). In conclusion the snapshot of follicular phase dietary protein requirement conformed with previous estimates for men, but was higher than previous nonempirical estimates for endurance-training women; low self-selected energy and carbohydrate intakes may explain the higher than expected nitrogen turnover, and consequently protein requirement.